MYC or BCL2 copy number aberration is a strong predictor of outcome in patients with diffuse large B-cell lymphoma - Lu, Ting-Xun (Oncotarget, 2015)
Diffuse large B-cell lymphoma (DLBCL) is the most common non-Hodgkin lymphoma (NHL). Patients with DLBCL harboring MYC aberrations concurrent with BCL2 or/and BCL6 aberrations constitute a specific group with extremely poor outcome. In this study, we retrospectively investigated the incidence and prognosis of MYC, BCL2, and BCL6 aberrations with DLBCL patients in Chinese population. We applied fluorescence in situ hybridization and immunohistochemical analysis in 246 DLBCL patients. The results showed that patients with MYC or BCL2 copy number aberration (CNA) had significantly worse overall survival (OS) and progression-free survival (PFS) than negative cases (P < 0.0001). Patients with both MYC and BCL2 CNA had similar outcomes to those with classic double hit lymphoma or protein double expression lymphoma (MYC and BCL2/BCL6 coexpression). By multivariate analysis, MYC CNA, BCL2 CNA and double CNA were the independent worse prognostic factors. In conclusions, patients with MYC or BCL2 CNA constituted a unique group with extremely poor outcome and may require more aggressive treatment regimens.